PENGARUH KOMPENSASI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT DIPO INTERNASIONAL PAHALA OTOMOTIF DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Amadi, Jam'an (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
The aim of this research is to determine the effect of compensation and job training on employee performance at PT Dipo Internasional Pahala Otomotif with job satisfaction as an intervening variable. The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The population in this study was all 97 employees in the company. The sampling technique used was a saturated sample where the entire population was used as the research sample. The analysis technique used is multiple linear analysis. The test results show that partially or simultaneously the compensation and job training variables have a positive and significant effect on employee performance with job satisfaction as an intervening variable.